EXOTIC FRUITS AND VEGETABLE FOOD AS NUTRITIONAL SUPPLEMENT FOR DIABETES, OBESITY AND METABOLIC DISEASES - JOSHI, SHRADDHA; JADHAV, VARSHA; KADAM, VILASRAO (International Journal of Current Pharmaceutical Research, 2018)
The most challenging diseases such as obesity and diabetes are growing wider and its treatment is aÂ major challenge for healthcare professionals. Most of these metabolic diseases are because of the impact of lifestyle on health. Many studies have recognized a high intake of fruits, greens and other vegetables, nuts and pulses play an important role in our daily diet. Biological constituents are important to combat such diseases and can act as nutritional supplements for treatment of diabetes, cancer, obesity and cardiovascular diseases. The aim of this article is to explore the role of all these exotic fruits and vegetable food in the pathophysiology of metabolic diseases and in alteration of diabetes and obesity.